Deradicalising violent extremists counter-radicalisation and deradicalisation programmes and their impact in muslim majority states - El-Said, Hamed; Harrigan, Jane (Routledge, 2013)
Terrorism remains one of the major threats facing the world community. While literature on the subject is dominated by discussion of the factors leading individuals and groups to join violent extremist, terrorist groups, the question of what can lead them to disengage from such groups is an equally important one. This book is the first study to provide a detailed analysis of both counter-radicalization and deradicalization programmes in eight Muslim-majority states, representing hitherto one of the largest, detailed, and most systematic inventory of such programmes in the world.